2018
DOI: 10.1590/abd1806-4841.20185489
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotection in adolescents: what they know and how they behave

Abstract: BackgroundThe greatest sun exposure occurs until adolescence and this is the only factor involved in photocarcinogenesis subject to modification with photoprotection.ObjectiveThe objective of this study was to evaluate the habits and knowledge of adolescents regarding photoprotection.MethodCross-sectional study that included 512 students from primary and high school. Data were collected by questionnaires with questions about habits and knowledge on sun protection. For data analysis, Pearson's Chi-square test a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
1
12
0
1
Order By: Relevance
“… 6 In spite of this, knowledge of the risks associated with sun exposure remains insufficient among children and adolescents. 7 , 8 Similar quantitative data have been reported for Reunion Island by the local association MiSolRé (Mission Soleil Réunion), which has been running sun safety campaigns in elementary schools since 2017. 9 , 10 The aim of this qualitative study was to explore the attitudes, barriers, and motivations to sun protection in Reunion Island with a view to proposing sun protection measures adapted to three populations: teachers, children, and parents.…”
Section: Introductionsupporting
confidence: 65%
“… 6 In spite of this, knowledge of the risks associated with sun exposure remains insufficient among children and adolescents. 7 , 8 Similar quantitative data have been reported for Reunion Island by the local association MiSolRé (Mission Soleil Réunion), which has been running sun safety campaigns in elementary schools since 2017. 9 , 10 The aim of this qualitative study was to explore the attitudes, barriers, and motivations to sun protection in Reunion Island with a view to proposing sun protection measures adapted to three populations: teachers, children, and parents.…”
Section: Introductionsupporting
confidence: 65%
“…The most appropriate time to introduce photoprotection habit is during childhood, which is the period of greatest sun exposure 14,16 . Like many studies, although most (93.5%) of our study participants reported knowing the harmful effects of sunlight, regular use of sunscreen was low (27.4%) 7,14,16,17 …”
Section: Discussionmentioning
confidence: 61%
“…Questionnaires were given to the student that addressed socioeconomic issues [29], a self-assessment of their phototype [30], and their knowledge and habits on PhP [21,31]. Illiterate children were helped by parents or guardians during meetings held at the schools.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that, regardless of age, profession, and income, PhP habits among individuals are inadequate, even in more developed countries with more robust educational systems [20,21,22,23]. By contrast, the cosmetics industry has reported increased sales of sun creams, which may be related to aesthetic factors related to excessive exposure to the sun, e.g., photoaging, freckles, and wrinkles [24].…”
Section: Introductionmentioning
confidence: 99%